تدريب المحادثة الأسبوعية لترقية مهارة الكلام (دراسة تحليلية عن طلاب معهد عرفة للتربية الإسلامية الحديثة سونجي فنوه) (Al-IRTIQA: Journal of Arabic Education and Linguistics, 2025)
This study aims to understand the process and implementation of Arabic conversation training at Ar-Rifah Institute for Modern Islamic Education, to identify the advantages and disadvantages of conducting weekly Arabic conversation sessions, and to examine the outcomes of this training on students’ speaking skills at the institute. The researcher employed a qualitative descriptive-analytical method to provide an in-depth analysis of the weekly conversation training in improving speaking proficiency. A qualitative approach was used to facilitate the collection of information regarding the weekly conversation practice conducted at Ar-Rifah Institute for the enhancement of speaking skills. This research applies a qualitative descriptive analysis technique as a step to process the collected data. During the investigation of Arabic language learning at Ar-Rifah Institute, data were obtained through interviews with educators who play a role in implementing the Arabic language system at the institute. The weekly Arabic conversation training has significantly improved students’ Arabic speaking skills. The students are now able to speak correctly and accurately, have the confidence to interact using the Arabic language, and show strong motivation to learn Arabic. Moreover, this training has created an Arabic language environment within the institute, making Ar-Rifah Institute a model to be emulated by other institutions in the region.